2015
DOI: 10.1115/1.4029941
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Abrasive Wear Behavior of Functionally Graded Aluminum Composite

Abstract: Functionally graded Al–Si12Cu/10 wt.% B4Cp metal matrix composite (MMC) has been fabricated under stir casting process followed by horizontal centrifugal casting method. The casting of length 170 mm, outer diameter 160 mm, and thickness 16 mm was obtained under the centrifugal speed of 1000 rev min−1. The microstructural evaluation was carried out on the surfaces at distance of 3, 6, 9, and 11 mm from the outer periphery of the casting to ensure the distribution of reinforcement particles, and the surfaces at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 10 publications
5
14
0
Order By: Relevance
“…The load of 64 N at the interfaces produces crushing of the sand particles at the stage of initial contact with it and thereby the sand particles are effective in abrade the surface of the specimen which leads to more material removal. The further increase in load to 80 N makes greater crushing effect on the abrasive medium and therefore the sand particles gets reduce in their sizes, where the same behaviour is observed (Antonov et al 2012;Radhika and Raghu 2015). Thus, the compression of these downsized abrasive medium outcomes in more cutting and abrading action which increases the abrasion wear rate.…”
Section: Effect Of Load On Abrasive Wear Behavioursupporting
confidence: 67%
“…The load of 64 N at the interfaces produces crushing of the sand particles at the stage of initial contact with it and thereby the sand particles are effective in abrade the surface of the specimen which leads to more material removal. The further increase in load to 80 N makes greater crushing effect on the abrasive medium and therefore the sand particles gets reduce in their sizes, where the same behaviour is observed (Antonov et al 2012;Radhika and Raghu 2015). Thus, the compression of these downsized abrasive medium outcomes in more cutting and abrading action which increases the abrasion wear rate.…”
Section: Effect Of Load On Abrasive Wear Behavioursupporting
confidence: 67%
“…The centrifugal force allows more number of high density nickel coated SiC particles to be dispersed to the outer periphery. With the increased uniform distribution and high volume fraction of SiC particles, the hardness near the outer periphery was more and similar phenomenon was studied here [19,20]. The solidification occurred from outer periphery towards inner periphery of casting, while the pressure force acts from inner to outer in an opposing radial direction producing a squeeze effect.…”
Section: Hardness Measurementsupporting
confidence: 66%
“…Low hardness at inner surface is due to the presence of microporosities and fewer reinforcement particles causing the indenter to produce increased deformation on the surface. Hence, it is concluded that the varying concentration of reinforcement particles defines the hardness and gradient properties along the radial direction of the casting [19,20].…”
Section: Hardness Evaluationmentioning
confidence: 99%